Diagnosis Penyakit Pada Bawang Merah Dengan Menggunakan Metode Fuzzy Tsukamoto (Studi Kasus : UPTD. Pembibitan Ternak Dan Hijauan Makanan Ternak Kec. Singosari Malang) - Firmansyah Arif Maulana; Nurul Hidayat; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The onion is one of horticultural plant. The onions plant contain abundant substances that act as an antibiotic, stimulate the body cell growth, repress bacteria activity, and also contain vitamin B1. Some factors could affect farmer's harvest result, one of them is pest attack. In fact, many farmers don't know how to treat and detect the pest attack on their plants. Based on that case, the system â€œOnion Disease Diagnose Using Fuzzy Tsukamoto Method (Case Study: UPTD. Cattle Breeding and Green Animal Feed Kec. Singosari Malang)â€ was built in this research. Fuzzy Tsukamoto method was used to diagnose the disease of onion plant. The result of diagnosis in this system was an onion disease. This system testing used the disease data from BPTP Malang, East Java. The onion disease diagnose experiment result showed 80 % accuracy.